A 6-Year Follow-up Study of Vagus Nerve Stimulation Effect on Quality of Life in Treatment-Resistant Depression: A Pilot Study. Issue 4 (December 2018) - Trottier-Duclos, François; Desbeaumes Jodoin, Véronique; Fournier-Gosselin, Marie-Pierre; Richer, François; Desjardins, Nathalie; Tieu, Sylvie; Lespérance, Paul
Abstract : Objectives: Treatment-resistant depression (TRD) carries a major burden on those affected by this disease and significantly impacts their quality of life (QOL). Vagus nerve stimulation (VNS) has showed promising results on symptoms, but its impact on QOL remains underresearched. This study aims to evaluate the long-term effects of VNS on both QOL and clinical symptoms for TRD patients, through a naturalistic 6-year follow-up. Method: Outpatients with confirmed TRD were enrolled to receive VNS. None of the patients enrolled left the study or was lost at follow-up. Patients were evaluated at 1, 3, 6, 12, 24, 36, 48, 60, and 72 months for a total of 10 assessments using the 36 item Short Form questionnaire, Hamilton Rating Scale for Depression and Hamilton Anxiety Rating Scale. Results: Ten patients were enrolled with a mean age of 50 years. This study shows a clinically and statistically significant improvement of the mental QOL ( P = 0.012), physical QOL ( P < 0.002), depressive symptoms ( P < 0.001), and anxiety symptoms ( P < 0.001). Conclusions: This long-term naturalistic study is the first to demonstrate that the therapeutic effect of VNS on TRD goes beyond clinical symptoms to improve the daily QOL of those affected.